PERAN DINAS LINGKUNGAN HIDUP DALAM PENGENDALIAN PENCEMARAN AIR DI PERAWANG KABUPATEN SIAK TAHUN 2020 - Pratama, Irsyad; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The environment based on Article 1 point (1) of Law Number 32 of 2009 concerning Environmental Protection and Management states the unity of space with all objects, forces, conditions, and living things, including humans and their behavior, which affect nature itself, the continuity of life , and the well-being of humans and other living things. Water pollution is one of the most common pollutions in various regions because water is a basic need for human life on this earth. In accordance with its use, water is used as drinking water, water for sanitation and water for transportation, both in rivers and at sea. Water is also used to improve the quality of human life, namely to support industrial and technological activities. The purpose of this study is to analyze the role of the environmental service in controlling water pollution and to analyze the obstacles in implementing the role of the environmental service in controlling water pollution in Siak Regency. The method used in this research is qualitative methodBased on the results of the study, it shows that the role of the Environmental Service in Controlling Water Pollution in Perawang has not been effective, because water pollution is still happening and there are still complaints from the public about polluted water. In addition, there are also obstacles such as: a) Lack of appropriate human resources in the field and expertise in water pollution, b) Limited funds which make it difficult for the government and the Environment Service to tackle water pollution, and c) Waste water treatment facilities are not yet available. sufficient to make the disposal of the waste still in the location of the local residents' land. Keywords: The Role of the Environmental Service, Water Pollution